2020
DOI: 10.1007/s42729-020-00382-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Techniques of Soil Management on Soil Fertility and the Associated Bacterial Communities in Semi-arid Olive Tree Fields

Abstract: A remarkable decrease in olive production has been observed in Tunisia since 2000, particularly in the semi-arid region. This downfall was mainly due to a notable change in climatic conditions as a result of wind erosion and over cultivation. The aim of this work was to study the biological, physical, and chemical properties of several semi-arid soils from olive tree fields subjected to different farming practices, such as crop time and type of crop, olive mill wastewater (OMW) application rates, and tillage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In both orchard soils, we found that the resident total bacterial community was largely affiliated with ubiquitous Actinobacteria and Proteobacteria (especially copiotrophic (Janssen 2006) including Mediterranean orchard soils (Curiel Yuste et al 2014;Siles et al 2014;Bastida et al 2017;Rajhi et al 2020). These taxa are widely distributed, inhabit nutrient-rich soils, participate in C, N, and S cycling, drive organic matter turnover and decomposition, regulate soil-plant interactions, release extracellular enzymes, and produce secondary metabolites (Spain et al 2009;Fausto et al 2018).…”
Section: Phylogenetic Diversity Of Indigenous Soil Bacteriamentioning
confidence: 83%
“…In both orchard soils, we found that the resident total bacterial community was largely affiliated with ubiquitous Actinobacteria and Proteobacteria (especially copiotrophic (Janssen 2006) including Mediterranean orchard soils (Curiel Yuste et al 2014;Siles et al 2014;Bastida et al 2017;Rajhi et al 2020). These taxa are widely distributed, inhabit nutrient-rich soils, participate in C, N, and S cycling, drive organic matter turnover and decomposition, regulate soil-plant interactions, release extracellular enzymes, and produce secondary metabolites (Spain et al 2009;Fausto et al 2018).…”
Section: Phylogenetic Diversity Of Indigenous Soil Bacteriamentioning
confidence: 83%
“…Regarding olive agroecosystems, it has been shown that organic amendments increase bacterial richness without affecting fungal richness [17]. Conversely, the use of fresh organic amendments such as oil mills wastewater, combined with other agricultural methods such as tillage, shows an increase in bacterial biomass but a reduction in bacterial diversity in the semiarid soils of olive groves [18] Additionally, shifts in soil microbial community composition have been associated with seasonality and sampling date in Mediterranean ecosystems, often linked to changes in soil management [19,20]. Understanding the role of both is critical to elucidate their effect on microbial biodiversity.…”
Section: Introductionmentioning
confidence: 99%